2021
DOI: 10.4049/jimmunol.2001130
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Efficacy and Anti-Inflammatory Mechanisms of Action of the Bruton Tyrosine Kinase Inhibitor Rilzabrutinib for Immune-Mediated Disease

Abstract: Bruton tyrosine kinase (BTK) is expressed in B cells and innate immune cells, acting as an essential signaling element in multiple immune cell pathways. Selective BTK inhibition has the potential to target multiple immune-mediated disease pathways. Rilzabrutinib is an oral, reversible, covalent BTK inhibitor designed for immune-mediated diseases. We examined the pharmacodynamic profile of rilzabrutinib and its preclinical mechanisms of action. In addition to potent and selective BTK enzyme and cellular activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
89
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(95 citation statements)
references
References 35 publications
1
89
1
2
Order By: Relevance
“…There is ongoing research involving Bruton's tyrosine kinase inhibitors in the potential treatment of immunerelated diseases. 96 Rilzabrutinib is an oral, reversible small molecule selective BTK inhibitor that has shown preclinical efficacy in rapidly inhibiting antibody mediated innate immune response as well as antibody production, exhibiting potential for ITP treatment. 96 Rilzabrutinib was also shown to be safe and well tolerated in a phase I trial, with favorable pharmacokinetics that could result in fast onset of effect.…”
Section: Therapies Currently Under Investigationmentioning
confidence: 99%
See 1 more Smart Citation
“…There is ongoing research involving Bruton's tyrosine kinase inhibitors in the potential treatment of immunerelated diseases. 96 Rilzabrutinib is an oral, reversible small molecule selective BTK inhibitor that has shown preclinical efficacy in rapidly inhibiting antibody mediated innate immune response as well as antibody production, exhibiting potential for ITP treatment. 96 Rilzabrutinib was also shown to be safe and well tolerated in a phase I trial, with favorable pharmacokinetics that could result in fast onset of effect.…”
Section: Therapies Currently Under Investigationmentioning
confidence: 99%
“…96 Rilzabrutinib is an oral, reversible small molecule selective BTK inhibitor that has shown preclinical efficacy in rapidly inhibiting antibody mediated innate immune response as well as antibody production, exhibiting potential for ITP treatment. 96 Rilzabrutinib was also shown to be safe and well tolerated in a phase I trial, with favorable pharmacokinetics that could result in fast onset of effect. 97 Bortezomib is a proteasome inhibitor that was shown in a preclinical study to improve thrombocytopenia in ITP by inducing apoptosis in long-lived plasma cells which were thought to play a role in corticosteroid resistant ITP.…”
Section: Therapies Currently Under Investigationmentioning
confidence: 99%
“…The reactivity of this complex confers a possibility to reverse the reaction under in vitro and cellular conditions ( 47 , 48 ). Pre-clinical studies of rilzabrutinib indicated anti-inflammatory effect in animal models of immune-mediated diseases ( 49 ).…”
Section: Btk Inhibitorsmentioning
confidence: 99%
“…A significant advantage of rilzabrutinib is that only short exposure is required to get a clinical benefit ( 27 ). Low systemic exposure reduces side effects, increases tolerability and promotes effectiveness and drug survival.…”
Section: Rilzabrutinib Biologymentioning
confidence: 99%
“…The activation of macrophages and monocytes via cross-linking of IgG and FcgR is a BTK dependent function; the ability of rilzabrutinib to prevent IgG mediated FcgR activation was illustrated in rodent models of lupus nephritis and immune thrombocytopenia (ITP). Rilzabrutinib has shown a unique dual Ab mechanistic approach over the standard treatments for immune-mediated diseases, based on its fast action on halting self-reactive Ab signaling and its longer-term impact on the formation of new autoantibodies ( 27 ).…”
Section: Rilzabrutinib Biologymentioning
confidence: 99%